2011
DOI: 10.1123/ijspp.6.4.455
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cluster Loading on Force, Velocity, and Power During Ballistic Jump Squat Training

Abstract: Purpose:The purpose of this study was to investigate the effect of set structure, in terms of repetition workrest ratios on force, velocity, and power during jump squat training.Methods:Twenty professional and semiprofessional rugby players performed training sessions comprising four sets of 6 repetitions of a jump squat using four different set configurations. The first involved a traditional configuration (TR) of 4 × 6 repetitions with 3 min of rest between sets, the second (C1) 4 × 6 × singles (1 repetition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 27 publications
7
26
0
1
Order By: Relevance
“…Lastly, previous studies have shown that the redistribution of rest periods maintains the kinetic and kinematic characteristics of resistance training ( Hansen et al, 2011 ; Moreno et al, 2014 ; Oliver et al, 2016 ), and the data in the present study also support those findings. Although there were no statistical differences between variables when all 36 repetitions were averaged together within each protocol, it is important that the strength and conditioning professional be cognizant of the competing physiological mechanisms of fatigue and potentiation, and consider the protocol x repetition interaction patterns of velocity and power output when rest periods are redistributed within a protocol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lastly, previous studies have shown that the redistribution of rest periods maintains the kinetic and kinematic characteristics of resistance training ( Hansen et al, 2011 ; Moreno et al, 2014 ; Oliver et al, 2016 ), and the data in the present study also support those findings. Although there were no statistical differences between variables when all 36 repetitions were averaged together within each protocol, it is important that the strength and conditioning professional be cognizant of the competing physiological mechanisms of fatigue and potentiation, and consider the protocol x repetition interaction patterns of velocity and power output when rest periods are redistributed within a protocol.…”
Section: Discussionsupporting
confidence: 91%
“…There is a lack of PF data within the cluster set literature, but previously, Hardee et al (2012) showed that PF was better maintained when longer inter-repetition rest periods were used during three cluster sets of six power cleans performed with a load of 80% of 1RM. On the other hand, Hansen et al (2011) showed that PF was not different between rest redistribution protocols during four sets of six jump squats with a fixed load of 40 kg. Considering that one study implemented extra rest periods during a heavily loaded concentric movement, whereas the other redistributed the total rest time during a relatively light exercise with a countermovement, it would be difficult to compare the PF results of either of those studies to the data in the present study.…”
Section: Discussionmentioning
confidence: 83%
“…CLU produced less metabolic stress, but produced a similar anabolic hormone response as measured by TT and FT. Further, despite lower TT in UT, similar responses were observed in all other variables of interest across subjects. Significantly greater power output in CLU was not an unexpected outcome as others have reported similar findings (Hansen et al 2011;Hardee et al 2012b;Joy et al 2013); however, in those studies, total volume load was equated between conditions. CLU resulted in greater average power while allowing for a greater total volume load in both RT and UT subjects, which is a novel aspect of the current study.…”
Section: Discussionsupporting
confidence: 49%
“…This intensity was selected as others have shown beneficial effects of CLU at these intensities following a period of training (Izquierdo et al 2006;Oliver et al 2013). Further, the total rest time was selected to equate rest between conditions (Hansen et al 2011). Seven days separated the trials.…”
Section: Experimental Designmentioning
confidence: 99%
“…When the same study implemented 52.5 s of rest between 9 sets of 4 repetitions, only 28 of the 36 repetitions were performed above the 20% velocity-decrease threshold, indicating that more frequent rest periods are beneficial for maintaining movement velocity when the total rest time and number of repetitions are equal. Paradoxically, that study [ 14 ] as well as many others have utilized either the same loads for all subjects [ 12 , 23 ] or loads relative to a subject’s 1 repetition maximum (1RM) [ 5 , 13 , 24 ], but aim to investigate the effects of cluster sets on maximizing power-output, with no studies utilizing loads that maximize power output [ 6 , 11 , 25 , 26 ]. As power output varies between exercises and individuals, it would be logical to utilize loads at which an individual’s maximum power output occurs when determining the effects of cluster sets on power output.…”
Section: Introductionmentioning
confidence: 99%